2019
DOI: 10.1155/2019/4851431
|View full text |Cite
|
Sign up to set email alerts
|

Lats2-Underexpressing Bone Marrow-Derived Mesenchymal Stem Cells Ameliorate LPS-Induced Acute Lung Injury in Mice

Abstract: The pathophysiology of the acute lung injury (ALI) is characterized by the damage of alveolar epithelial cells, which can be repaired by exogenous bone marrow-derived mesenchymal stem cells (BMSCs). However, the migration and differentiation abilities of BMSCs are not sufficient for the purpose, and a new approach that could strengthen the repair effects of BMSCs in ALI still needs to be clarified. We have previously proved that in vitro large tumor suppressor kinase 2- (Lats2-) underexpressing BMSCs may enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…In addition, miR-23a-3p downregulation was previously found to be associated with LPS-induced rat testis (12), while miR-23a-3p upregulation was detected in acute laminitis horses (27). Our study demonstrated that LPS-induced ALI markedly downregulated miR-23a-3p expression, and similar to Dong's findings (28), it also increased LWW/BW, promoted inflammatory infiltration and enhanced inflammatory factor release in vivo.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, miR-23a-3p downregulation was previously found to be associated with LPS-induced rat testis (12), while miR-23a-3p upregulation was detected in acute laminitis horses (27). Our study demonstrated that LPS-induced ALI markedly downregulated miR-23a-3p expression, and similar to Dong's findings (28), it also increased LWW/BW, promoted inflammatory infiltration and enhanced inflammatory factor release in vivo.…”
Section: Discussionsupporting
confidence: 87%
“…Severe ALI leads to life-threatening respiratory failure with high morbidity and mortality [ 54 , 55 ]. Infiltration of inflammatory cells, increased blood-air barrier permeability, pulmonary edema, and diffuse alveolar damage are often found in ALI [ 54 , 56 , 57 ]. Meanwhile, excessive lung inflammation and apoptosis of alveolar epithelial cells (AECs) are key factors in the pathogenesis of ALI [ 52 , 56 ].…”
Section: The Hippo Signaling Pathway and Respiratory Diseasesmentioning
confidence: 99%
“…Moreover, alveolar epithelial cells are repaired by exogenous bone marrow-derived mesenchymal stem cells (BMSCs) and down-expression of LATS2 improves BMSCs repairing the tissue in ALI, thereby alleviates the pathological damage of lung tissue [ 57 ]. In addition, inhibition of hippo signaling pathway increases BMSCs retention and migration to the site of injured lung tissue and promoted the differentiation of BMSCs into AECIIs [ 57 ].…”
Section: The Hippo Signaling Pathway and Respiratory Diseasesmentioning
confidence: 99%
“…Numerous studies provide evidence to demonstrate a therapeutic effect of bone marrow mesenchymal stem cells (BMSCs) in various clinical disorders, including ALI, in which BMSCs prevent tissue injury through different mechanisms [8,9]. Recently, several researches have indicated that the BMSCs secrete specialized membranous nanosized vesicle termed exosomes to prevent lung tissue injury [10][11][12].…”
Section: Introductionmentioning
confidence: 99%